Rehabilitation of Small‐Diameter Cast‐Iron Pipe: US, UK, and Australian Perspectives. Issue 1 (1st January 2015) - Marlow, David; Gould, Scott; Beale, David; Lane, Bradley
Abstract : Cast‐iron pipe is commonly found in water supply networks across the globe. Because these pipelines are legacy assets, utilities typically conduct annual rehabilitation programs to renovate or replace a portion of these pipes. Although the traditional approach involves open‐cut procedures, various trenchless renovation and replacement techniques can be used, although their use is less common in the United States than in some other English‐speaking countries. Research was thus undertaken to consider the differences in attitudes toward rehabilitation of small‐diameter (4–8 in., or 100–200 mm) cast‐iron pipe in the United States, Australia, and the United Kingdom. Survey and interview‐based techniques were used to generate case studies of existing practices. The results suggest that preferences and assumptions about the relative value of different techniques play a significant role in decision‐making. Though conflicting views were expressed, the researchers concluded that renovation and trenchless replacement techniques should be selected when they provide significant life‐cycle cost savings and are technically feasible.